Peningkatan pemasaran produk turunan peternakan dan pertanian melalui pemanfaatan marketplace digital di Desa Mundu Kabupaten Klaten - Susilawati, Sukma Ayu; Oftasari, Yosi; Salsabila, Fina; Andriyani, Nur (Penamas: Journal of Community Service, 2025)
Developing rural economies that focus on village independence through small and medium-sized enterprises (SMEs) entrepreneurship provides significant benefits for the community and local government. By improving access to production resources, technology, and capital, it is hoped that the production and productivity of the community will increase, along with the realization of welfare through product sales and the creation of new jobs in the agrotourism, handicrafts, and tourism sectors. Mundu Village, Tulung District, Klaten Regency, has entrepreneurial potential from livestock and agricultural products. However, low digital literacy among business actors poses a major challenge. This community service aims to enhance digital literacy through training and assistance in creating WhatsApp Business, TikTok, and Instagram accounts. The methods of socialization and training are expected to encourage improved product marketing, ultimately enhancing the welfare of the village community. Program results indicate a 40% increase in understanding of social media marketing, a 32.4% increase in the use of digital marketplaces, and a 13.4% increase in WhatsApp Business. With support from digital technology, local products from Mundu Village are expected to compete in a broader market.